A preliminary study of movement intensity during a Go/No-Go task and its association with ADHD outcomes and symptom severity. Issue 1 (December 2016) - Li, Fenghua; Zheng, Yi; Smith, Stephanie; Shic, Frederick; Moore, Christina; Zheng, Xixi; Qi, Yanjie; Liu, Zhengkui; Leckman, James
Abstract Objective At present, there are no well-validated biomarkers for attention-deficit/hyperactivity disorder (ADHD). The present study used an infrared motion tracking system to monitor and record the movement intensity of children and to determine its diagnostic precision for ADHD and its possible associations with ratings of ADHD symptom severity. Methods A Microsoft motion sensing camera recorded the movement of children during a modified Go/No-Go Task. Movement intensity measures extracted from these data included a composite measure of total movement intensity (TMI measure) and a movement intensity distribution (MID measure) measure across 15 frequency bands (FB measures). In phase 1 of the study, 30 children diagnosed with ADHD or at subthreshold for ADHD and 30 matched healthy controls were compared to determine if measures of movement intensity successfully distinguished children with ADHD from healthy control children. In phase 2, associations between measures of movement intensity and clinician-rated ADHD symptom severity (Clinical Global Impression Scale [CGI] and the ADHD-Rating Scale IV [ADHD-RS]) were examined in a subset of children with ADHD (n = 14) from the phase I sample. Results Both measures of movement intensity were able to distinguish children with ADHD from healthy controls. However, only the measures linked to the 15 pre-determined 1 Hz frequency bands were significantly correlated with both the CGI scores and ADHD-RS total scores. Conclusions Preliminary findings suggest that measures of movement intensity, particularly measures linked to the 10–11 and 12–13 Hz frequency bands, have the potential to become valid biomarkers for ADHD.